Synthesis and Purification of Acamprosate Calcium and its Evaluation by RP-HPLC in Pharmaceutical Dosage Forms: Synthesis and Purification of Acamprosate Calcium and its Evaluation by RP-HPLC - Rezaei, Mehdi; Ramazani, Ali; Gouranlou, Farideh (Iranian Journal of Pharmaceutical Sciences, 2020)
The purpose of this study is Acamprosate Calcium synthesis of 3-Aminopropane-1-sulfonic acid (Homotaurine) and validation of assay test in the delayed-release tablets by HPLC without organic solvents. The assay method by HPLC was found to be linear in the concentration range of 50 to 200 μg/mL. Successful separation was achieved by isocratic elution on a Phenomenex® C18 column (250 mm × 4.6 mm, 5μm).The mobile phase was triethylammonium phosphate buffer pH: 4.0 (100%) at the flow rate of 1 mL/min using UV detection at 210 nm, column oven temperature 25ºC and injection volume 20